Mutagenic improvement of Bacillus cereus resistant to Ralstonia solanacearum - ZHANG Min; TANG Zhi-liang; SHU Kai; ZHAO Dan-ping; HU Xiao (浙江大学学报. 农业与生命科学版, 2010)
To improve the resistance of Bacillus cereus to Ralstonia solanacearum, an antagonistic bacterium belonging to B. cereus, named as L1, was isolated from the ginger-growing soil, which was resistance to R. solanacearum at some degree. Ultraviolet rays (UV), ethyl methane sulfonate (EMS) and acridine orange (AO) were used as mutagens to treat strain L1, and then the mutants were identified and screened. The results showed that the antagonistic abilities of mutant strains were significantly enhanced compared with the original strain L1, and the concentrations of antagonistic protein of mutant-strains EMS-2 and UL-1, were 30.38% and 29.18% higher than that of original strain L1 separately, being significant difference between the two mutant-strains and L1. In addition, strain L1 was sensitive to UV especially during the period of 60 s, and up to 90 s, the utmost positive mutation rate was detected (24.8%). However, no positive mutants were founded when the strain L1 was treated with AO. Moreover, the lethal rate of strain L1 was up to 90% with the treatment of EMS beyond 80 min, indicating that to obtain the more number of positive mutants, the lower dosage of EMS (0.16 mol· mL-1) for longer treatment time (60 min) was the possible method of mutant treatment.